Relationship among psychological well-being, resilience and coping with social and clinical features in Crohn's disease patients - Acciari, Arlete Silva; Leal, Raquel Franco; Coy , Cláudio Saddy Rodrigues; Dias, Cristiana Corrrêa; Ayrizono, Maria de Lourdes Setsuko (Seven Editora, 2023)
Introduction: Crohn's disease is chronic, requires prolonged treatment, affects the physical and psychosocial health of patients and may alter their routine, quality of life and well-being. Recent studies recommend monitoring the health of these patients considering physical, psychological and psychosocial aspects, because they are directly related to the disease activity. These studies highlight the relevance of patients' emotional and behavioral conditions and suggest that the identification of the factors that influence the psychological well-being, resilience and Coping in these patients can favor the proper treatment. Objective: To relate psychological well-being, resilience and Coping with social and clinical features of Crohn's disease patients. Method: Prospective study including 104 patients with Crohn's disease, both genders and mean age of 39 years. Standardized scales were used to assess and to relate psychological well-being, resilience and Coping with social and clinical variables. A questionnaire to characterize the sample and standardized scales in data collection (psychological well-being, resilience pillars and Coping strategies inventory - Folkman & Lazarus) werw used. Descriptive analysis of data and statistics for comparison of results were performed. Results: There were significant differences (p< 0.05) showing better psychological well-being for male patients, those who without children, were not religious, were employed and were doing complementary activities in addition to clinical treatment. More resilience for the male gender, those who without children, were not religious, divorced, separated or widowed, that received some monthly income; who did not undergo surgery, had the first symptoms after 30 years old and who had complementary activity. There were also significant differences in the use of Coping: usually, women used more developed escape and avoidance strategies; single, married or in stable-union patients used more self-control; not religious used positive revaluation strategy; the ones who were employed showed more self-control and positive reassessment; the ones who had lower family income indicated that they used less the self-control; the ones who had higher family income used more positive re-evaluation; patients who were diagnosed with Crohn's disease between the second decade of life showed to use mores more the positive reassessment strategy than those who were 20 years old or younger. Conclusion: Social aspects influenced psychological well-being, resilience and Coping in patients with Crohn's disease more strongly than clinical aspects. It was possible to identify the profiles with better and worse psychological well-being, resilience and Coping of those who need more support, as well as to know the most used Coping strategies in the studied group. DOI:https://doi.org/10.56238/cienciasaudeestuepesv1-068